Islamic Waqf in Yemen and its Economic Effects - Al-Hattami, Thekra Mohammed (Journal of Humanities & Social Sciences, 2023)
This study mainly aims to show the economic effects Waqf (Endowment). It deals with the concept of Waqf in the language and the terminology from the perspective of the Faqihs who the concept of Waqf differed in their wording and agreed in its meaning. Moreover, the types of Waqfs in Yemen were highlighted and that Waqf, in all stages performed its full functions in the development of socity. So, the Waqf proves to be the most successful economic means if the Waqf funds are invested in the right way. The Waqf beneficiaries benefited from it in order to the right achieve the purpose of the Waqf giver. That all was done by using the descriptive method. The study concluded the following results and recommendations: 1.Waqif is of an important role that could be useful for community economically, educationally and socially . 2.Assuring the importance of Waqif in the whole system of development through sheding light on the historical Islamic civilization in Yemen.